Mesoporous Carbon Produced from Tri-constituent Mesoporous Carbon-silica Composite for Water Purification - Yu, Yanjie (2013)
Highly ordered mesoporous carbon-silica nanocomposites with interpenetrating carbon and silica networks were synthesized by the evaporation-induced tri-constituent co- assembly approach. The removal of silica by concentrated NaOH solution produced mesoporous carbons, which contained not only the primary large pores, but also the secondary mesopores in the carbon walls. The thus synthesized mesoporous carbon was further activated by using ZnCl2. The activated mesoporous carbon showed an improved surface area and pore volume. The synthesized mesoporous carbon was tested for diuron removal from water and the results showed that the carbon gave a fast diuron adsorption kinetics and a high diuron removal capacity, which was attributable to the primary mesopore channels being the highway for mass transfer, which led to short diffusion path length and easy accessibility of the interpenetrated secondary mesopores. The optimal adsorption capacity of the porous carbon was determined to be 390 mg/g, the highest values ever reported for diuron adsorption on carbon-based materials.